#TITLE_ALTERNATIVE# - LUTHFI RAMADHAN (NIM: 25313023), MUHAMMAD
Shrimp culture activity has contribution on nitrogen loading in water. Nitrogen loading is related with nitrogen waste release to water from residue of feed and shrimp metabolism product. Prediction was done to quantify the quantity of nitrogen loading by using computer model. Quantification of nitrogen loading was arranged through various approaches on actual conditions. Approaches of actual condition were formulated to be mathematical equation to develop model computer then to predict the quantity of the nitrogen loading from overall intensive shrimp culture activity. In this study, calculation was started by making a basic calculation of nitrogen loading in one pond. The result of calculation was processed then to be a regression equation to get mathematical equation of nitrogen loading in one pond. This equation was assumed can be applied for all pond in the study area. Further calculation of nitrogen loading was done by integrating mathematical equation of nitrogen loading in pond, number of operational pond and water balance of study area into a model computer. The equation that applied to quantify nitrogen loading was y = 0.611x2 - 1.719x + 1.932, where y is mass of nitrogen and x is period of culture. Based on prediction by using computer model, the quantity of nitrogen loading in run-off was about 2,666 kg.year-1 with run-off volume was about 362,789 m3.year-. Whereas the quantity of the nitrogen loading that released in harvest time was about 14.613 kg.year- with water volume was about 785.700 m3.year- and nitrogen concentration on wastewater was about 19.8 ppm. Based on the simulation results, nitrogen loading that produced from intensive shrimp culture activity can be reduced by decrease the protein content of feed and increase the feed conversion. Result of simulation by adjusting the harvest time showed that the change of the harvest time has no significant effect on decreasing the nitrogen loading that produced from the activity, but it can stabilize the quantity of the nitrogen loading in water.